Finite element investigation of some aspects affecting the depth and wall thickness of a part formed by single point incremental forming process. (1st January 2012) - Echrif, Salah B.M.; Hrairi, Meftah
Single point incremental forming (SPIF) is an emerging sheet-metal-forming technology, capable of manufacturing complex parts at low cost for small to medium-batch production. The present paper is focused on using finite element analysis to study the phenomenon of overstretch the wall thickness along depth and the effect of the tool path on the distribution of the wall thickness.